EBV-associated mucocutaneous ulcer, a rare cause of a frequent problem. Issue 4 (7th April 2020) - Hess, Gabriel Fridolin; Menter, Thomas; Boll, Daniel; Steiger, Jürg; von Strauss und Torney, Marco
Abstract: This report presents a 74-year-old renal transplant patient suffering of polymorphic-post-transplant-associated lymphoproliferative disease (P-PTLD) within an Eppstein-Barr Virus (EBV) associated mucocutaneous rectal ulcer (MCU). He was initially treated by stapled hemorrhoidopexy for a symptomatic grade III hemorrhoidal prolapse refractory to conservative treatment and rubber band ligations. This leads to severe urge, frequency and stool fragmentation. The symptoms were investigated with a number of interventions until a proctoscopy with biopsies finally revealed the diagnosis. The patient had triple therapy of tacrolimus, mycophenolate mofetil and prednisone initially after transplant several years ago with recent reduction to mycophenolate. The MCU was successfully treated with Retuximab and there was no sign of relaps after 6 months. As EBV-associated PTLD is a well known complication after renal transplant, rectum-MCU seems a rare and only recently described subform of this disease that should be excluded in case of ulcerating lesions in immunosuppressed patients.